The role of suspicion in B2B customer entertainment. Issue 5 (6th June 2016) - Oakley, Jared; Bush, Alan J.
Abstract : Purpose: The purpose of this paper is to conduct an exploratory study of potential business-to-business (B2B) customers that includes an empirical analysis that investigate the effect that customer entertainment has on customer suspicion toward the salesperson, and how those negative attitudes are influenced by the relationship stage and the perceived cost of the event. Design/methodology/approach: Using an experimental design, data were collected from 105 potential customers working in a B2B environment that assessed their attitudes regarding offers of varying levels of customer entertainment across differing stages of the relationship. Findings: Results demonstrate that B2B customers have important perceptions regarding the perceived cost of customer entertainment offers by salespeople. Those evaluations resulted in a positive relationship between customer attitudes of suspicion toward the salesperson and the perceived cost of the entertainment event. However, the stage of the relationship tended to ameliorate suspicious attitudes of customers, although not in a completely symmetrical manner. Research limitations/implications: Additional testing with larger sample populations would better solidify the existence of the relationships. Practical implications: This study provides a framework for practitioners that gives direction to the strategic use of customer entertainment such that it acts as a relationship catalyst, and not a relationship poison. Originality/value: The paper uses a customer perspective to fill a need to better understand the instrumental role of customer entertainment in relationship marketing, and how it interacts with the perceived cost of the event and relationship stage to create differing customer attitudes.